2017
DOI: 10.3319/tao.2017.03.20.02
|View full text |Cite
|
Sign up to set email alerts
|

Shallow geological structures triggered during the Mw 6.4 Meinong earthquake, southwestern Taiwan

Abstract: The Meinong earthquake generated up to ~10 cm surface displacement located 10 -35 km west of the epicenter and monitored by InSAR and GPS. In addition to coseismic deformation related to the deep earthquake source, InSAR revealed three sharp surface displacement gradients. One of them is extensional and is inconsistent with the westward interseismic shortening of ~45 mm yr -1 in this region. The gradient sharpness suggests slip triggering on shallow structures, some of which were not well documented before. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 42 publications
(70 reference statements)
0
31
0
1
Order By: Relevance
“…Seismic Lines D1 and D5, as well as D6 and rD1 (Figure a), located north of the Tainan Tableland, image a pure‐shear fault‐bend fold developing on an ~38°W dipping back thrust, interpreted as the continuation of the Houchiali fault, that roots on a 3.8‐km‐deep subhorizontal detachment within the Lower Gutingkeng mudstone. This detachment is referred to as the Tainan detachment (Le Béon et al, ). The fold appears to have vanished at the latitude of Seismic Line rD2 (Figure a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seismic Lines D1 and D5, as well as D6 and rD1 (Figure a), located north of the Tainan Tableland, image a pure‐shear fault‐bend fold developing on an ~38°W dipping back thrust, interpreted as the continuation of the Houchiali fault, that roots on a 3.8‐km‐deep subhorizontal detachment within the Lower Gutingkeng mudstone. This detachment is referred to as the Tainan detachment (Le Béon et al, ). The fold appears to have vanished at the latitude of Seismic Line rD2 (Figure a).…”
Section: Discussionmentioning
confidence: 99%
“…The Holocene shortening rate that we determined accounts for 25% of the regional shortening rate, making the anticline and the Houchiali fault a significant active structure at the scale of the fold‐and‐thrust belt. In contrast, the fold inception age of 310 ± 50 ka is very young, and the cumulative shortening of 2–3 km is limited in regard of the ~3‐Ma deformation history of the foothills (Le Béon et al, ; Mouthereau et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12)than that of far filed stations. It also implies that the horizontal displacement is mainly controlled by the foldand-thrust system connected with N-S trending shallow dé-collement (Le Béon et al 2017). This triggering of coseismic slip from the shallow structure was also highlighted by Lin et al (2016) in 2010 Jiashian earthquake.…”
Section: Triggered Slip From Shallow Structures From Meinong Earthquakementioning
confidence: 96%
“…By integrating all these information, they concluded that multiple pre-existing blind faults were reactivated during the 2016 Meinong earthquake sequences. Based on surface and subsurface geology and geodetic observations during the 2016 Meinong earthquake, Le Béon et al (2017) built two E-W balanced cross-sections to identify the shallow structures that may have been reactivated during the earthquake. They interpreted these activated structures as a series of west-dipping back-thrust ramps connected to the westward-propagating Tainan detachment.…”
mentioning
confidence: 99%